Urinary incontinence (UI) in older women in low- and middle-income countries: a rapid review and case study from Burkina Faso - Kozhumam, Arthi; Bountogo, Mamadou; Palmer, Dina Goodman; Grieg, Carolyn; Inghels, Maxime; Agyapong-Badu, Sandra; Osborne, Cristina; Harling, Guy; Bärnighausen, Till; Rapp, David; Beestrum, Molly; Davies, Justine; et al. (Frontiers in Global Women's Health, 2025)
The prevalence of urinary incontinence (UI) in older women in low- and middle-income countries (LMICs) is not well understood. We conducted a rapid literature review to assess the burden of UI in this population and contextualize findings from a household survey of women aged 40 and older in Nouna, in northwestern Burkina Faso. The rapid review included 21 survey articles. UI prevalence for LMIC women 40 or older varied greatly (6%–80%), with differences by socio-demographics, gynecological factors (menopausal status, birth outcomes), comorbidities (age, education, obesity, diabetes, hypertension, arthritis), behaviors (smoking status) and survey location. The studies used validated tools—the International Consultation on Incontinence Urinary Incontinence Short Form (ICIQ UI-SF) was most common (n = 4, 19%)—and bespoke tools that have not yet been validated. In Nouna, 983 (64.5%) of 1,524 women, completed the ICIQ UI-SF. Overall UI prevalence, defined as reporting leakage at least 2–3 times a week, was 2.6% (95% CI 1.73%–3.85%), descriptively increased with age from 0.5% in 40–49 year-olds to 6.6% in those 70 and over. Of those with UI, 88.5% experienced leakage daily, and 50% reported moderate or greater interference with daily life, yet most (88.5%) had not spoken to a healthcare provider. Multivariable analysis revealed that UI was more common among women who were not currently married and decreased with higher education levels. Both the rapid review and survey highlight the burden of UI among older women in LMICs, particularly as they age beyond 60. Given UI's association with physical and mental health, it is crucial to raise awareness of its burden, improve healthcare access, and integrate routine screening into basic healthcare services. Additionally, training healthcare providers and developing culturally appropriate interventions will help address stigma and ensure effective management of UI in this vulnerable population.